The Effect of Education Using the Health Belief Model Approach on Mother’s Behavior in Preventing Malnutrition for Toddlers Aged 1-3 Years - Ernawati, Naya; Purnamasari, Intan; Hidayah, Nurul; Astuti, Erlina Suci (Journal La Medihealtico, 2024)
Toddlers are the age group most often and prone to suffering from malnutrition or malnutrition. One of the causes of high malnutrition is the lack of public awareness in health care, especially mothers for their toddlers and monotonous counseling methods. One way to improve toddler health care can be done by providing education to mothers with various models, one of which is using the Health Belief Model approach. Education with the Health Belief Model approach provides a strong relevance between health education and behavior change. To find out the Effect of Education Using the Health Belief Model Approach on Mother's Behavior in Preventing Malnutrition in Toddlers Aged 1-3 Years at Posyandu Mawar, Kalipare Village, Malang Regency. This study used a pre-experimental design with a one group pretest and posttest design approach. The population of this study were mothers who had toddlers aged 1-3 years with malnutrition and at risk of 75 respondents who were then taken using a purposive sampling technique which obtained 42 respondents. The results of statistical tests using the Wilcoxon signed rank test obtained the value of Sig. (2-tailed) p-value = 0.00 (p <0.05) which means that there is an effect of education using the Health Belief Model approach on maternal behavior in preventing malnutrition in toddlers aged 1-3 years at Posyandu Mawar, Kalipare Village, Malang Regency . It is hoped that this research can be used to improve maternal behavior in preventing malnutrition in toddlers aged 1-3 years.